2020
DOI: 10.1177/0193945920957229
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Symptom Burden of Hemodialysis Patients

Abstract: This cross-sectional study assessed the overall symptom burden, including the prevalence, frequency, severity, and distress of symptoms among hemodialysis patients, and explored the relationship between demographic characteristics, clinical variables, self-management, sense of coherence, social support, and symptom burden in these patients. Herein, a regression analysis was performed to determine associations with symptom burden. The mean score of symptom burden among the participants (n = 382) was 74.12, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
(55 reference statements)
0
7
0
2
Order By: Relevance
“…When patients’ evaluation or expectation was inconsistent with their actual experience, uncertainty arose, which made the patients unable to determine the impact of diseases and dialysis related complications and symptoms those therapy targeted, worried about the treatment effect and prognosis, and lead to anxiety and depression(Yan et al., 2012 ). MHD patients often experience various symptoms and these ambiguous symptoms were severe, erratic, but often were underestimated and without adequate treatment(Song et al., 2020 ). Besides, the variety of symptoms among patients with ESRD made patients hard to build correct perceptions of illness which increased patients’ negative feelings and decline in QoL.…”
Section: Discussionmentioning
confidence: 99%
“…When patients’ evaluation or expectation was inconsistent with their actual experience, uncertainty arose, which made the patients unable to determine the impact of diseases and dialysis related complications and symptoms those therapy targeted, worried about the treatment effect and prognosis, and lead to anxiety and depression(Yan et al., 2012 ). MHD patients often experience various symptoms and these ambiguous symptoms were severe, erratic, but often were underestimated and without adequate treatment(Song et al., 2020 ). Besides, the variety of symptoms among patients with ESRD made patients hard to build correct perceptions of illness which increased patients’ negative feelings and decline in QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the dual effects of the disease itself and hemodialysis treatment, patients often experience a variety of symptoms such as fatigue, dry skin, sleep disorders, muscle cramps, itching, and other physical symptoms, as well as psychological symptoms such as anxiety, worry, and depression, which impose a huge burden on patients’ lives [ 6 , 7 ]. Because older patients are prone to multiple chronic conditions and functional impairment, their symptom burden is heavier and their health-related quality of life (HRQOL) is worse than that of younger patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis patients may lose confidence in treatment and affect prognosis due to long treatment cycle and irreversible course [ 3 , 4 ]. Clinically, whether some effective intervention measures can be used to improve the maintenance quality of arteriovenous fistula in hemodialysis patients and ultimately improve the quality of dialysis is considered, but there are few relevant literatures [ 5 , 6 ].. Studies have shown that the correct nursing is an important factor affecting the survival period of fistula [ 7 , 8 ].. Traditional nursing methods lack systematicness and pertinence.…”
Section: Introductionmentioning
confidence: 99%